2013
DOI: 10.1007/s10803-013-1824-9
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor Type 2, but not Type 1, is Up-Regulated in Peripheral Blood Mononuclear Cells of Children Affected by Autistic Disorders

Abstract: Autistic disorders (ADs) are heterogeneous neurodevelopmental disorders arised by the interaction of genes and environmental factors. Dysfunctions in social interaction and communication skills, repetitive and stereotypic verbal and non-verbal behaviours are common features of ADs. There are no defined mechanisms of pathogenesis, rendering curative therapy very difficult. Indeed, the treatments for autism presently available can be divided into behavioural, nutritional and medical approaches, although no defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
100
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 59 publications
13
100
0
1
Order By: Relevance
“…These drugs could potentially ameliorate the epilepsy-related symptoms that commonly co-occur with ASD. On a final note, it seems of major interest that preliminary data, showing consistency between changes in distinct eCB system elements (i.e., CB 2 ) in animal models of ASD and in peripherabl blood mononuclear cells from young patients with ASD [106,107], support a role for these elements in the (early) diagnosis of the disease. Future work should test expression profiles for key players of the eCB system in prospective samples to test the potential of these as diagnostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These drugs could potentially ameliorate the epilepsy-related symptoms that commonly co-occur with ASD. On a final note, it seems of major interest that preliminary data, showing consistency between changes in distinct eCB system elements (i.e., CB 2 ) in animal models of ASD and in peripherabl blood mononuclear cells from young patients with ASD [106,107], support a role for these elements in the (early) diagnosis of the disease. Future work should test expression profiles for key players of the eCB system in prospective samples to test the potential of these as diagnostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, genomic studies have highlighted an upregulation of mRNA levels of the CB 2 A, but not the CB 2 B, isoform in the cerebellum of BTBR T+tF/ J mice [105], which have an autism-like behavioral phenotype [106]. Also, an independent clinical study performed on young (3-9-year-old) children demonstrated that CB 2 is highly expressed, both at transcriptional and translational levels, in peripheral blood mononuclear cells of patients with autism, compared with matched healthy controls [107]. All the other elements of the eCB system remained unaltered, except for a The reduced empathy is therefore a product of this reduced attention to social stimuli.…”
Section: Alterations Of the Ecb System In Autismmentioning
confidence: 99%
“…Accordingly, sulfation deficits in acetaminophen (paracetamol) metabolism with the autism population could indirectly increase the endocannabinoids levels, which in turn are able to activate CB1/2 receptors triggering autism. Endocannabinoid-CB2 signalling dysregulation has been reported in monocytic cells extracted from autistic children [2]. More interesting, blood monocyte-derived macrophagic cells from autistic patients also reveal EC system dysregulation, further indicating the involvement of the EC system in autism associated immunological disruptions and pointed to a potential nexus between endocannabinoids, vitamin D and the immune dysregulations observed with autism [8].…”
mentioning
confidence: 87%
“…Recently, several studies highlight a key involvement of endocannabinoid (EC) system in autism pathophysiology [2].…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation